ANALYSIS OF FACTORS AFFECTING DIVIDEND POLICY IN BANKING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE WITH MANAGERIAL OWNERSHIP AND INDEPENDENT COMMISSIONERS AS MODERATING VARIABLES - Fernandes, Fredrick (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to examine and analyze the factors that influence dividend policy and to test managerial ownership and independent commissioners as moderating variables in banking companies listed on the Indonesia Stock Exchange. This study uses a causality method with a population and at the same time a sample of 43 companies by determining the sampling method using the saturated sampling method. Hypothesis testing uses panel data regression with a test tool using the E-Views application. The results showed that profitability, debt policy, collateralizable assets, and earnings per share simultaneously had a significant effect on dividend policy in banking companies listed on the Indonesia Stock Exchange. Partially, only profitability does not affect dividend policy, while debt policy, collateralizable assets, and earnings per share have a significant effect on dividend policy. Managerial ownership as a moderating variable is not able to moderate the relationship of variable profitability, debt policy, collateralizable assets and earnings per share to dividend policy. While independent commissioners as moderating variables are able to moderate the relationship of profitability, debt policy, collateralizable assets, and earnings per share to dividend policy.